The Long-Run Impact of Sovereign Yields on Corporate Yields in Emerging Markets - Li, Delong (IMF Working Papers; Working Paper ;, 2021)
We analyze the long-run impact of emerging-market sovereign bond yields on corporate bond yields, finding that the average pass-through is around one. The pass-through is larger in countries with greater sovereign risks and where sovereign bonds are more liquid. It is also greater for corporate bonds with lower ratings, shorter maturities, and for those issued by financial companies and government-related firms. Our results support theoretical arguments that corporate and sovereign yields are linked together through credit risks and liquidity premiums. Consequently, high sovereign risks may slowdown growth by persistently increasing private sector borrowing costs.